Fighting crimes in the customs field is an important factor of ensuring economic security - Gafurov Farkhod Rashidovich (Zien Journals, 2023)
In this scientific article, the issues of improving the organizational and legal basis of investigative activities in the detection of customs crimes in the Republic of Uzbekistan today are explained. In particular, practical and legal problems in the detection of crimes in the customs field and proposals for their solution are described.
Keywords: customs crime; operational-search activity; operational-search activities; violation of customs legislation